Beak deformities in north Patagonian birds - Gorosito, Cristian Andrés (2016)
Within the last decade, many individuals of several bird species with abnormal and strange beaks deformations have been reported from Alaska, United States, and from United Kingdom and Ireland. Different forms of beak deformities were observed, but the causes of these abnormalities are unknown. We report beak deformities in two species of birds in northwestern Patagonia, Argentina: Austral Thrush (Turdus falcklandii) and Patagonian Mockingbird (Mimus patagonicus). Between 2013 and 2016, we captured individuals of White‐crested Elaenia (Elaenia albiceps, N = 305), Rufous‐collared Sparrow (Zonotrichia capensis, N = 119), Austral Thrush (N = 100), Black‐chinned Siskin (Spinus barbata, N = 64), Patagonian Sierra‐Finch (Phrygilus patagonicus, N = 48) and Gray‐hooded Sierra‐Finch (Phrygilus gayi, N = 40) in surroundings of Esquel city, located in western Patagonia, Chubut province, and quantified the prevalence of beak deformities. Only adult Austral Thrushes (5 out of 78; 6.41%) showed abnormal beaks. Neither juvenile thrushes (N = 22) nor the other five species showed beak deformations. Austral Thrushes with beak deformations were also observed and photographed (but not captured) in other areas around the city. We also photographed one Patagonian Mockingbird with an abnormal beak near Las Plumas Village, Chubut province. Beak deformities varied from light to severe, and also in their form. Most of them were characterized by an elongated and often decurved upper mandible, producing an overbite; in other individuals both mandibles were elongated and sometimes crossed or had a pronounced gap. Most affected birds showed signs of improper preening, and one of them was malnourished. All of these characteristics are similar to those described for birds affected by avian keratin disorder in North America. Further research is needed to detect potential presence of other species with beak deformities in Patagonia, to find out possible causes of such deformities, and to determine whether these anomalies are associated with natural habitats or urban environments.